Endourology Methods in Pediatric Population for Kidney Stones Located in Lower Calyx: FlexURS vs. Micro PCNL (MicroPERC®) - Halinski, Adam; Steyaert, Henri; Wojciech, Magdalena; Sobolewski, Bartłomiej; Haliński, Andrzej (Frontiers in Pediatrics, 2021)
Kidney stone disease in children is always a therapeutic challenge. It is a multifactorial condition and it should be approached, diagnosed and treated as such. One of the biggest challenges is kidney stones located in the lower renal calyx. There are currently three main surgical techniques to treat this condition: ESWL—Extracorporeal Shock Wave Lithotripsy, RIRS—Retrograde IntraRenal Surgery, and PCNL—PerCutaneous Nephro-Lithotripsy. In pediatric population, the most frequently used method is ESWL, and in the event of failure, endoscopic procedures are the second-best choice. In this article, a sample of 53 children admitted to a tertiary medical center was examined. Thirty-eight of those children underwent flexible URS, while the remaining 15—micro PCNL. The average size of the deposit in the former group was 12.2 mm, against 13.5 mm in the latter. The full Stone Free Rate (SFR) was achieved in RIRS at 84.21 and 86.7% in percutaneous nephrolithotripsy. Flexible ureterorenoscopy and MicroPERC are two comparably effective methods for treating lower calyx stones of any size. However, according to our data, flexible ureterorenoscopy carries a lower risk of complications and inpatient care (with the mean of 3 days). The learning curve for these procedures in pediatric urology is long and relies on a limited number of patients. The number of pediatric patients qualifying for these procedures is restricted also due to the high efficacy of extracorporeal shock wave lithotripsy in pediatric population. Radiation exposure is an important factor in every endoscopy procedure and should never exceed the limits set in the ALARA protocol. ESWL remains to this day the treatment of choice for stone disease in children and can be performed under ultrasound control. For many parents, it is a first-choice treatment preference for their child due to its greater apparent safety, although data on this remains insufficient. Prospective, randomized, multicenter trials are definitely needed.